TWEAK regulates proliferation and differentiation of adult neural progenitor cells - Schölzke, Marion Nicola; Röttinger, Amely; Murikinati, Sasidhar Reddy; Gehrig, Nadine; Leib, Christoph; Schwaninger, Markus (Molecular and cellular neuroscience, 2011)
The cytokine TWEAK is expressed in the brain and is induced in cerebral ischemia and other brain disorders. TWEAK regulates proliferation and differentiation of progenitor cells but its effect on adult neural progenitor cells is still unknown. Therefore, we investigated the proliferation of neural progenitor cells from the subventricular zone of adult mice in response to TWEAK treatment. TWEAK inhibited proliferation of neural progenitor cells through its membrane receptor Fn14. The reduced proliferation was not due to cell death. By using a reporter assay we found that TWEAK activated the transcription factor NF-κB in adult neural progenitor cells. Blockade of NF-κB signaling reversed the inhibition of cell proliferation by TWEAK. In addition, TWEAK induced neuronal differentiation of neural progenitor cells and lowered the expression of hes1, a transcription factor that prevents neuronal differentiation. In adult mice deficient of the TWEAK receptor Fn14, neurogenesis was reduced in the subventricular zone. In conclusion, our data show that TWEAK regulates adult neurogenesis in the subventricular zone by binding to the membrane receptor Fn14 and activating NF-κB.